(untitled) (Philological Studies, 2023)
This paper looks whether the key terms of the representational - syntactic and pragmatic categories can also be applied in the study of traditional visual narratives, as a sign system with certain symbolic messages. We believe that the answer to this question fully corresponds to the basic postulates and methods of semiology, as a science of the study of signs and the symbols and the mutual relations that they establish, i.e. bearers of the sign and the signified (designatuma/ denotatuma), where each individual object can imply certain signs. In the context of this, we showcase several examples of embroidery, a selection from Macedonian folk costumes, which we believe correspond visually and semiologically with Jung’s mandalas. They are presented in this text as images with certain symbolic values, which speaks in favor of the power of the collective memory of a nation, group or community that consciously or subconsciously integrated its spiritual, aesthetic and cultural values ​​into its collective consciousness. This phenomenon indicates that this is an archaic cultural matrix, close to the ontological, universal values ​​of man in a wider cultural, temporal and areal context. Hence, we consider that the polystadiality of folklore, which contains different layers of mythology, history and tradition of a given community, is not only characteristic of different literary-narrative folklore forms, but is also applicable in the study of "visual narratives" (decorative patterns, motifs and ornaments), represented in the traditional material culture of peoples around the world.